Sensing time and potential in a speed skating development program. (2nd September 2022) - Jacobs, Sarah
ABSTRACT: Based in ethnographic fieldwork among high-performance speed skaters, this paper considers some of the structures and experiences of athlete development and training. As a racing sport, fast times in speed skating matter. Yet time is not simply quantified. It is also felt in various ways. There are qualities to time. Time is taken into the body and expended from the body. Inspired by Nancy Munn's contributions to temporalization, I explore time's embodiment, its strategic use, and the moral evaluations of time within speed skating. I further consider how potential underpins various temporal engagements and enactments, including the sequence of athlete development, cycles and rhythms of training and the experience of tapering prior to competition. Both time and potential, I argue, are sensed in the broadest meaning of that term. Lastly, I consider how the timely management of potential demands faith, suggesting that athletes and coaches have much in common with speculators in financial markets.